216k views
4 votes
Solve for g.
-3+5+6g=11-3g−3+5+6g=11−3g

User Richardun
by
4.9k points

2 Answers

6 votes

Answer:
\mathrm{No\:Solution}

Explanation:


\begin{bmatrix}-3+5+6g=1\\ 1-3g+5+6g=11-3g\end{bmatrix}


\begin{bmatrix}1-3\left(-(1)/(6)\right)+5+6\left(-(1)/(6)\right)=11-3\left(-(1)/(6)\right)\end{bmatrix}


\begin{bmatrix}(11)/(2)=(23)/(2)\end{bmatrix}


(11)/(2)=(23)/(2)\:\mathrm{\:is\:false,\:therefore\:the\:system\:of\:equations\:has\:no\:solution}

User Gerardo Grignoli
by
4.8k points
4 votes

Answer:

g=1

Explanation:

User DNF
by
4.7k points